Women's Intentions to Become Acceptors in Family Planning Post Covid-19: Theory of Planned Behavior - Mujahidah, Rd. Gita (Indonesian Journal of Global Health Research, 2024)
Post-Covid-19 shows that the level of contraceptive use and the need for family planning cannot be met at both the district and city levels, seen from the large variations that show disparities in the implementation of family planning programs, this causes stagnation in the number of contraceptive use and the need for family planning is not met in Indonesia. During the pandemic, there was a decrease in the use of contraceptives and an increase in unplanned pregnancies. Intention is an important component in generating behavior. A person can carry out or not carry out a behavior depending on that person's intentions, so that the attitude of women of childbearing age towards carrying out family planning depends on their intentions. This study aims to see a picture of the intentions of women of childbearing age to become family planning acceptors. Descriptive research method with a population of women of childbearing age in Indramayu Regency who were selected using simple random sampling totaling 83 people. Data collection was carried out by respondents filling out a questionnaire developed by researchers referring to guidelines for making instruments based on the Theory of Planned Behavior and analyzed using statistical tools. The research results show that the intention of women of childbearing age in carrying out family planning after Covid-19 has a strong intention of 86.7% and a weak intention of 13.3%. So, from the results of this research, it is important for nurses to pay attention to the intentions of women of childbearing age in carrying out family planning and to develop strategic health promotion that can reach all groups.